Leptospirosis and malaria as causes of febrile illness during a dengue epidemic in Jamaica. (1st September 2013) - Lindo, John; Brown, Paul D; Vickers, Ivan; Brown, Michelle; Jackson, Sandra T; Lewis-Fuller, Eva
Abstract : Background: Epidemics of febrile illnesses are often associated with rainy seasons in the tropics. During 2007-2008 an epidemic of dengue was identified in Jamaica based on serological testing of sera. Methods: A subset of 3165 of 5400 sera submitted for dengue analysis was tested for Leptospira IgM and malaria IgG using ELISA to determine their role in causing epidemic fever. Findings: Seropositivity for dengue, leptospirosis, and malaria were 38·4 and 6·0 and 6·5%, respectively, indicative of three concurrent epidemics. Mixed exposure to all three diseases was rare (0·1%), as were mixed dengue/malaria (2·4%); dengue/leptospirosis (1·6%), and leptospirosis/malaria (0·03%) exposure. Exposure to dengue and malaria appeared to occur most frequently among children while leptospirosis was more common among adults. Conclusion: While serological diagnosis definitively established that dengue was the main cause of the epidemic febrile illness, the data suggested that there may be other causes of fever, which may occur simultaneously. Consequently, leptospirosis and malaria should be considered as causes of fever during epidemics of dengue in endemic areas.